Does serum vitamin D level affect the association between cardiovascular health and cognition? Results of the Cardiovascular and Metabolic Diseases Etiology Research Center (CMERC) study. (27th September 2020) - Jeon, Y. J.; Jung, S. J.; Kim, H. C.
Abstract : Background and purpose: Few studies have assessed the role of vitamin D in the association between cardiovascular risk factors and cognitive function. Here, the aim was to investigate the association between cardiovascular health (CVH) and cognitive function according to vitamin D level in a middle‐aged Korean population. Methods: This cross‐sectional study included 840 men and 1811 women (mean age 57.2 years) from the Cardiovascular and Metabolic Diseases Etiology Research Center study baseline enrolment (2013–2018). Life's Simple 7 tools from the American Heart Association were used to assess CVH. Cognitive function was evaluated using the Mini‐Mental State Estimation for Dementia Screening (MMSE‐DS), and the serum 25‐hydroxyvitamin D level was measured. Results: In the adjusted generalized linear regression models, no significant association between a high Life's Simple 7 score (4–7 metric at optimal level) and MMSE‐DS score ( β  = 0.01, P  = 0.93) was found. Amongst men with a high vitamin D level, the high Life's Simple 7 score group showed a significantly higher MMSE‐DS score ( β  = 0.48, P  = 0.03). However, amongst men in the low vitamin D group, the association was opposite with no statistical significance ( β = −0.23, P  = 0.08). In women, the results were similar, but both strata according to vitamin D level showed no statistical significance. Conclusions: Our findings suggest that vitamin D is an effect modifier in the association between CVH and cognition, especially in men. Abstract : Interaction between Life's Simple 7 (LS7) score and serum vitamin D level estimating MMSE‐DS, stratified by gender ( N  = 2651).